2020
DOI: 10.1038/s41598-020-71817-x
|View full text |Cite|
|
Sign up to set email alerts
|

Simultaneous molecular MRI of extracellular matrix collagen and inflammatory activity to predict abdominal aortic aneurysm rupture

Abstract: Abdominal aortic aneurysm (AAA) is a life-threatening vascular disease with an up to 80% mortality in case of rupture. Current biomarkers fail to account for size-independent risk of rupture. By combining the information of different molecular probes, multi-target molecular MRI holds the potential to enable individual characterization of AAA. In this experimental study, we aimed to examine the feasibility of simultaneous imaging of extracellular collagen and inflammation for size-independent prediction of risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Ferumoxytol is not only used in imaging techniques for tumor diseases but may also have applications in cardiovascular diseases [ 21 , 22 , 44 ] and the central nervous system [ 15 ]. Different studies have investigated the molecular properties of cardiovascular disease with a combined approach using iron-oxide nanoparticles and a gadolinium-based contrast agent [ 21 , 22 , 44 ]. A limitation that needs to be considered regarding ferumoxytol is that it is not prostate tumor specific or even tumor specific.…”
Section: Discussionmentioning
confidence: 99%
“…Ferumoxytol is not only used in imaging techniques for tumor diseases but may also have applications in cardiovascular diseases [ 21 , 22 , 44 ] and the central nervous system [ 15 ]. Different studies have investigated the molecular properties of cardiovascular disease with a combined approach using iron-oxide nanoparticles and a gadolinium-based contrast agent [ 21 , 22 , 44 ]. A limitation that needs to be considered regarding ferumoxytol is that it is not prostate tumor specific or even tumor specific.…”
Section: Discussionmentioning
confidence: 99%
“…It emphasized the role of collagen components in maintaining aneurysm structure integrity and prompted a great possibility of taking it as a prediction biomarker for future study. Future collagen‐specific MRI may aid the evaluation of BBA rupture prediction 26 …”
Section: Discussionmentioning
confidence: 99%
“…It is reported that an increased replacement of ECM collagen without adequately matched collagen deposition is a critical factor for AAA rupture in the dissection ( Jana et al, 2019 ; Adams et al, 2020 ). There are various underlying mechanisms implicated in the pathogenesis of AAA, including ECM degradation.…”
Section: Discussionmentioning
confidence: 99%